Regulatory T cells but not NKT I cells are modulated by a single low-dose Cyclophosphamide in a B cell lymphoma tumor-model - Rico, M.J.; Rozados, V.R.; Mainetti, L.E.; Zacarias Fluck, M.F.; Matar, P.; Scharovsky, O.G. (Experimental Oncology, 2012)
Aim: Experimental and clinical studies showed that the administration of cyclophosphamide (Cy) in low doses leads to an enhancement of the antitumor immune response. Our objective was to study the modulation, if any, by low dose Cy, of T regulatory (Treg) and natural killer T (NKT) I cells, two cell populations of the innate immune response with opposing effects on the tumors, in a rat B cell lymphoma model. Methods: Inbred e rats were challenged s.c. with L-TACB lymphoma and on day 14 animals were distributed in two groups. Treated: injected i.p. with cyclophosphamide (10mg/kg of body weight) and Control: injected i.p. with saline. Blood samples were taken from days 0 to 21 and the percentage of T regulatory and natural killer T I cells were determined by flow cytometry. Results: We found that the increase of natural and inducible T regulatory cells of peripheral blood achieved during tumor growth was significantly downregulated by cyclophosphamide. On the contrary, natural killer T I cells were not modulated by the treatment. Conclusion: The antimetastatic effect of a single low dose of Cy would be due, at least in part, to downregulation of natural and inducible T regulatory cells.